PSIII-33 A new approach to resynchronize beef cows and perform two Timed Artificial Inseminations 24 days apart. (5th December 2019) - Colli, Marcos A; Cline, Garrett; Walker, Josh; Forrest, David; Baruselli, Pietro S; Looney, Charles
Abstract: We aimed to compare the pregnancy rate from 1 st TAI and 2 nd TAI performed 24 days apart and pregnancy between cows that showed or not estrous on the end of 2 nd TAI protocol. Were used 190 lactating cows (Angus: 114; Brangus: 53 and Santa Gertrudis: 23). On the first day of synchronization (D0), insertion of a new CIDR® (Zoetis) plus the 100µg of Cystorrelin®(Merial) treatment, on D7 25mg of Lutalyse® (Zoetis) and CIDR withdrawal. 72 hours after CIDR removal 1 st TAI was performed plus GnRH treatment. After 14 days from 1 st TAI, all the cows received an one time used CIDR. The pregnancy diagnosis was performed 22 days after 1 st TAI, using a subjective visual evaluation of CL blood flow (BF). Pregnancy diagnosis was performed by ultrasonography Color Doppler (MicroMaxx®). Cows with an area of CL≥3cm² and/or ≥25% CL BF were diagnosed as pregnant and underwent CIDR removal without further treatment. Those diagnosed as non-pregnant underwent CIDR removal and received one Estrotect™ (Rockway-Inc.), 25mg of Lutalyse treatment and submitted to 2 nd TAI 48h after CIDR removal (D24) plus the 100µg of Cystorrelin. On D31 considered pregnant cows on D22 were examined by US B-mode D31 to verify false positive and effective pregnancies. On D55, cows were submitted to US B-mode to verify the 2 nd TAI pregnancy rate. Statistical analysis were performed using GLIMMIX procedure from SAS. The pregnancy on D22 was 48.5% (87/190) and the false positives were 14.9% (13/87). There was no difference on pregnancy 31 days after 1 st TAI (38.9%; 74/190) vs. 2 nd TAI (32.0%; 33/103; P = 0.24). Cows were more likely to be pregnant on D55 compared to cows that: showed Estrous: 42.9% (21/49) vs. No Estrous: 22.2% (12/54; P = 0.03). In conclusion, the pregnancy rates were the same at 1 st to 2 nd TAI. And cows that showed estrous had more pregnancy at 2 nd TAI.